ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN KELAYAKAN USAHA AGROWISATA STRAWBERRY (Fragaria choiloensis L.) PETIK SENDIRI (Studi Kasus : Kabupaten Karo) - Muhammad JufriansyahMuhammad Jufriansyah; Gustami Harahap; Mitra Musika Lubis (Jurnal Agriuma, 2019)
In North Sumatra there  is  one  type  of  horticulture  plant,  strawberry,  especially  in Karo district. The purpose of this study  was  to  find  out  what  factors  influence  the  level  of income of strawberry picking agrotourism farmers themselves, knowing the price of their  own picking strawberry agro-tourism business and knowing whether the picking  strawberry  agro- tourism business itself is feasible. The sampling method is used  by  the  Central  theorem  limit method, the total population of strawberry farmers in Karo Regency  is  60,  in  this study 30 farmers were made as representative samples of the entire population. The data collected is primary  and  secondary  data.  The  analytical  method  used  is  multiple  linear  regression   with SPSS 21, BEP software tools and business feasibility analysis using  R  / C  Ratio.  (1) From the study using multiple linear regression analysis tools which have positive effect on strawberry farmers'  income,  namely  sales  and  expenditure  volume  of  RT.  (2)  Analysis  of  data  from (BEP), it is known that the sales  volume  reaches  the  level of 478.80 Kg with a selling price of  Rp. 52,760 / Kg, then the sales result is Rp. 38,304,239, with the results of the sale, the strawberry  picking  agro-business  itself  was  declared  even.  (3)  Analysis of the feasibility of the own strawberry picking agrotourism business in  Karo  Regency,  obtained  the  results  of R  / C> 1, then the business is economically feasible.